Upaya Meneguhkan Komitmen Beribadah Mahasiswa Di Era New Normal - Mavianti Mavianti (Al-Ulum: Jurnal Pendidikan Islam, 2021)
Pandemic cinditions is undeniable situation for all campuss residents, including students. It’s actually a learning they receive face to face but it has to turn into online learning. In this case of course it has a close relationship with the commitment of whorship for students, especially the new normal era. Because before pandemic the students were far from parents for the sake their higher education. But with the pandemic many students choose to go home because the learning is done online. In addition, they can help their parents while in the village. When close to parent is essentially a challenge in terms of commitment whorship. For students who already have a solid foundation early not problem wherever they are so that it remains consistent in performing whorship. But for students who have a less solid foundation should get more attention and motivation and support from their parents. In this case the role of parents needed so that the child gets the appropriate attention because in term of age, they are in such a poor condition that it gives to the desire to gain recognition and attention. And if they don’t get attention and recognition from their parents then they’ll look for outside. Such condition can trigger the appearance of adolescent arrogance. This pandemic condition will certainly further maximize the role of their children. Parents are more involved in the spiritual development of during online learning in the new normal era.Affirming, Worshiping, Students, New Normal Era